Pengaruh Faktor Perencanaan, Pelaksanaan dan Pengembangan Jasa Layanan Non Finansial Program Business Development Service (BDS) terhadap Kinerja Pengelola Usaha Kecil Menengah (UKM) di Kabupaten Aceh Utara dan Kota Lhokseumawe - Mariyudi -; Ikramuddin - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The aim of this research is to analyze the relationship of Business Development Service (BDS) and manager performance of SME in Aceh Utara and Lhokseumawe. The scope of the study is limited to the BDS program that including the relationship of planning, implementation and development to the management performance of SME. The multiple regressions was used to analyze the data. The result indicates that the BDS program has positive relationship to the manager performance of BDS in Aceh Utara and Lhokseumawe.Keywords: BDS, performance of SME, planning, implementation and development.